The Combination of Rhythm and Pitch Can Account for the Beneficial Effect of Melodic Intonation Therapy on Connected Speech Improvements in Broca’s Aphasia - Zumbansen, Anna; Peretz, Isabelle; Hébert, Sylvie (Frontiers in Human Neuroscience, 2014)
Melodic intonation therapy (MIT) is a structured protocol for language rehabilitation in people with Broca’s aphasia. The main particularity of MIT is the use of intoned-speech, a technique in which the clinician stylizes the prosody of short sentences using simple pitch and rhythm patterns. In the original MIT protocol, patients must repeat diverse sentences in order to espouse this way of speaking, with the goal of improving their natural, connected speech. MIT has long been regarded as a promising treatment but its mechanisms are still debated. Recent work showed that rhythm plays a key role in variations of MIT, leading to consider the use of pitch as relatively unnecessary in MIT. Our study primarily aimed to prospectively assess the relative contribution of rhythm and pitch in MIT’s generalization effect to non-trained stimuli and to connected speech. We compared a melodic therapy (with pitch and rhythm) with a rhythmic therapy (with rhythm only) and with a normally spoken therapy (without melodic elements). Three participants with chronic post-stroke Broca’s aphasia underwent the treatments in hourly sessions three days a week for six weeks, in a cross-over design. The informativeness of connected speech, speech accuracy of trained and non-trained sentences, motor-speech agility and mood was assessed before and after the treatments. The results show that the three treatments improved speech accuracy in trained sentences, but that the combination of rhythm and pitch elicited the strongest generalization effect both to non-trained stimuli and connected speech. No significant change was measured in motor-speech agility or mood measures, with neither treatment. The results emphasize the beneficial effect of both rhythm and pitch in the efficacy of original MIT on connected speech, an outcome of primary clinical importance in aphasia therapy.